Educar para o nunca mais: sequência didática, memória e esquecimento sobre a ditadura militar nos livros didáticos de história (2011-2017) - Jessica Machado de Souza (2018)
The core of this dissertation consists in the analysis of the perception of human rights show up in current textbooks, based on the period of the military dictatorship in Brazil and the practices of torture committed. In this way, the main objective, however in this work is to understand the subjects' perception of memory struggles, by problematizing the relation between basic education and human rights, as well as the conceptions present in the history´s textbooks. Considering that the period in question was and continue in the subject of disputes memories, it is important to analyze the role reflected in textbooks in the face of these disputes, especially due to the resurgence of conservative forces transposed into new demands of society. Considering the continuity of these clashes, as well as the need to 'Educate for never again', a didactic sequence was elaborated that allows the appropriation of the knowledge produced by the National Commission of Truth (CNV), allowing the recognition of the democratic values necessary for the full exercise of citizenship